Analisis Biplot pada Pemetaan Karakteristik Indeks Pembangunan Manusia (IPM) Kabupaten/Kota di Provinsi Jawa Timur tahun 2016 - artanti indrasetianingsih (J STATISTIKA: Jurnal Imiah Teori dan Aplikasi Statistika, 2018)
Characteristics of a region is a feature that is owned by the area. Characteristics can be seen from several aspects that exist in each region. East Java Province is a province located in the east of Java Island with Surabaya City as the Capital of Province. Biplot is one attempt to describe the data contained in the summary table in the two-dimensional graph. This analysis aims to model a matrix by overlapping vectors representing row vectors with vectors representing the vectors of the matrix column. Biplot analysis is based on the analysis of the main component (PCA biplot), ie by describing singular value or singular value decomposition (SVD). SVD aims to decipher the singular value of a matrix which is an nxp sized matrix that has been corrected with the mean and then raised the matrix and. The data used in this study using secondary data obtained from the Central Bureau of Statistics of East Java Province in 2016. Based on the result of data analysis, it can be concluded that 2 main factors are economic education consisting of infant mortality rate (X1), percentage of poor people (X2), per capita expenditure per year (X3), old school expectancy (X4) average of school length (X5) and social health factors consisted of percentage of population with appropriate drinking water source (X11), percentage of households living clean and healthy (X13).Goodness of fit biplot in economic education factor of 0.878. Karakteristik suatu wilayah merupakan ciri yang dimiliki oleh daerah tersebut. Karakteristik dapat dilihat dari beberapa aspek di masing-masing wilayah. Provinsi Jawa Timur merupakan sebuah provinsi di sebelah timur Pulau Jawa dengan Kota Surabaya sebagai Ibukota Provinsi. Biplot adalah salah satu upaya menggambarkan data-data yang ada pada tabel ringkasan dalam grafik berdimensi dua. Analisis ini bertujuan memperagakan suatu matriks dengan menumpang tindihkan vektor-vektor yang merepresentasikan vektor-vektor baris dengan vektor-vektor yang merepresentasikan vektor-vektor kolom matriks tersebut. Analisis biplot didasarkan pada analisis komponen utama (PCA biplot), yaitu dengan menguraikan nilai singular atau singular value decomposition (SVD). Data yang digunakan pada penelitian ini menggunakan data sekunder yang diperoleh dari Badan Pusat Statistik Provinsi Jawa Timur tahun 2016. Berdasarkan hasil analisis data maka dapat disimpulkan bahwa terbentuk 2 faktor utama yaitu faktor pendidikan ekonomi yang terdiri dari variabel angka kematian bayi (X1), persentase penduduk miskin (X2), pengeluaran per kapita per tahun (X3), harapan lama sekolah (X4), rata-rata lama sekolah (X5) dan faktor sosial kesehatan terdiri dari variabel persentase penduduk dengan sumber air minum layak (X11), persentase rumah tangga berperilaku hidup bersih dan sehat (X13). Goodness of fit biplot dalam faktor pendidikan ekonomi sebesar 87,8%.